Model-guided metabolic gene knockout of gnd for enhanced succinate production in Escherichia coli from glucose and glycerol substrates. (April 2016) - Mienda, Bashir Sajo; Shamsir, Mohd Shahir; Illias, Rosli Md
Graphical abstract: Highlights: Model-guided gnd gene knockout strategy was applied for the first time in Escherichia coli for increased succinate production. The model prediction of increased succinate production after gnd gene knockout was consistent with experimental data. Glucose and glycerol substrates were used for the prediction and the experimental validations. This strategy produced 1.4 g l −1 and 0.35 g l −1 of succinate from glycerol and glucose substrates respectively. Abstract: The metabolic role of 6-phosphogluconate dehydrogenase ( gnd ) under anaerobic conditions with respect to succinate production in Escherichia coli remained largely unspecified. Herein we report what are to our knowledge the first metabolic gene knockout of gnd to have increased succinic acid production using both glucose and glycerol substrates in E. coli. Guided by a genome scale metabolic model, we engineered the E. coli host metabolism to enhance anaerobic production of succinic acid by deleting the gnd gene, considering its location in the boundary of oxidative and non-oxidative pentose phosphate pathway. This strategy induced either the activation of malic enzyme, causing up-regulation of phosphoenolpyruvate carboxylase ( ppc ) and down regulation of phosphoenolpyruvate carboxykinase ( ppck ) and/or prevents the decarboxylation of 6 phosphogluconate to increase the pool of glyceraldehyde-3-phosphate (GAP) that is required for the formation of phosphoenolpyruvate (PEP). This approach produced a mutant strain BMS2 with succinic acid production titers of 0.35 g l −1 and 1.40 g l −1 from glucose and glycerol substrates respectively. This work further clearly elucidates and informs other studies that the gnd gene, is a novel deletion target for increasing succinate production in E. coli under anaerobic condition using glucose and glycerol carbon sources. The knowledge gained in this study would help in E. coli and other microbial strains development for increasing succinate production and/or other industrial chemicals.